The 21st Century Family in the Context of the Challenges of Modernity – Single Parenthood in Macro, Meso, and Micro Perspective - Jurczyk - Romanowska, Ewa (Pedagogika, 2013)
The purpose of the present paper is to compare three levels of discourse on the subject of the 21st century family. The macro scale is represented by the ideas of the International Year of the Family + 20, the meso scale – by the postulates of the government of Poland aimed at the implementation of international presumptions in Poland. The reality experienced by single parents and its inherent evaluation of the realization of the government’s postulates constitutes the micro scale. Comparison of the three perspectives allows for a discernment of the shortcomings of the government’s postulates as well as the somewhat superficial character of the undertaken actions.